THE PATRIOTIC COMPONENT WITHIN THE EDUCATIONAL-TRAINING PROCESS OF TRAINING OFFICERS OF THE ARMED FORCES OF UKRAINE - Kolesnik, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
In the scientific article the components of the theory of education are revealed: content, principles, methods and regularities of educational, patriotic training of future officers in the system of military education of Ukraine in accordance with modern political realities. The patriotism of soldiers, their feelings of love for the Fatherland, embodied in serving its interests, is of fundamental importance for the development of the Armed Forces of Ukraine.The main goal of higher military education today is to facilitate the forming of an officer - a national patriot, a high-level professional in his business, who can independently put up and solve professional problems in the so-called society of risk.Among the educational competences of officers the following are to be mentioned: the culture of systematic professional thinking, the culture of communication, the ability to work as part of a team, tolerance, striving for self-education and self-development, responsibility, organizational and leader qualities, firmness and sustainability to permanent changes of social and natural environment, flexible and creative thinking, spirituality, the appropriate style of professional behavior, the ability to present one’s personal and professional qualities, the culture of a healthy way of life.The methodological basis of the process of patriotic education of officers is the scientific theory of knowledge, which involves the unity of the historical and logical in the pedagogical process, the methodological analysis of didactic concepts, facts, phenomena in combination with the content of the methodology of training military officers, is the knowledge of the theoretical foundations of normative disciplines, the use of the cycle practical and tactical training. Objective point of this theory is recognition of objectivity and materiality of the surrounding world, its existence in constant motion, change and development, knowledge of the world and its laws. The basis of knowledge is the entire set of human practice, the means of human influence on nature and production relations.
Keywords: the theory of education of officers, patriotism, maintenance and principles of education, training of military personnel